Psychometric Properties of the Short Form of Watson-Glaser Critical Thinking (WGCTA-S)Appraisal among a Sample of Students Teachers - Khaled N. Al - Otaibi (Sultan Qaboos University, 2012)
The purpose of this study was to examine the psychometric properties of the Watson-Glaser Critical thinking Appraisal -Short form (WGCTA-S) - as a tool that measures critical thinking. It comprises 40 items that measure five skills: inference, recognition of assumptions, deduction, interpretation and evolution of argument within (16) different scenarios. The test was administered to a random sample of 400 students from the Teachers College. The results revealed that the (WGCTA-S) is a valid and reliable test. Factor analysis revealed five factors identifying the same factors of the original instrument. The correlation coefficients ranged between dimensions and total score for the test between (0.301 - 0.801) which shows the construct validity, and the reliability of test re-test was (0.78) and alpha was (0.80). The results of the study found differences between students of theoretical and scientific departments on (WGCTA-S) in the favor of the students of scientific departments. The study also found differences between students of high academic achievement and low academic achievement on (WGCTA-S) in favor of the of high academic achievement.